Respuesta :
Hey!
-------------------------------------------------
Solve:
= 2(a - 3) + 4b - 2(a - b - 3) + 5
Distributive Property:
= 2a - 6 + 4b - 2a + 2b + 6 + 5
Combine Like Terms:
= (2a - 2a) + (4b + 2b) + (6 - 6 + 5)
Simplify:
= (0a) + 6b + 5
Answer:
= 6b + 5
-------------------------------------------------
Hope This Helped! Good Luck!
Answer:
6b + 5
Step-by-step explanation:
2(a -3) + 4b - 2(a - b -3) + 5
2 * a = 2a
2 * -3 = -6
2a - 6 + 4b - 2(a - b - 3) + 5
-2 * a = -2a
-2 * -b = 2b
-2 * -3 = 6
2a - 6 + 4b - 2a + 2b + 6 + 5
Combine like terms
2a - 2a = 0
-6 + 4b + 2b + 6 + 5
4b + 2b = 6b
-6 + 6b + 6 + 5
-6 + 6 + 5 = 5
6b + 5